2019
DOI: 10.3389/fmed.2019.00085
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Correlation of Amyopathic Dermatomyositis With Fixed Sources of Airborne Pollution: A Retrospective Cohort Study

Abstract: Objective: Dermatomyositis (DM) may result from exogenous triggers, including airborne pollutants, in genetically susceptible individuals. The United States Environmental Protection Agency's 2011 National Air Toxics Assessment (NATA) models health risks associated with airborne emissions, available by ZIP code tabulation area (ZCTA). Important contributors include point (fixed), on-road, and secondary sources. The objective of this study was to investigate the geospatial distributions of DM and subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Although application of spatial point processes is more common in ecology ( 42 ), it is an emerging tool in epidemiological research ( 43 ). We observed clustering of IIM and its phenotypes in some regions, and a statistically nonsignificant effect of distance from road network on myositis prevalence, but a significant effect of RUCA, possibly indicating exposure to higher level of air pollutants, consistent with previous studies that also found a significant correlation between clinically amyopathic DM with airborne pollutants ( 22 ) and urban dwellings ( 7 ). More research is needed to understand the role of proximity to roadways and air pollutants, as well as other exposures and risk factors, in the development of myositis, given the geospatial distribution of myositis patients nationwide.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although application of spatial point processes is more common in ecology ( 42 ), it is an emerging tool in epidemiological research ( 43 ). We observed clustering of IIM and its phenotypes in some regions, and a statistically nonsignificant effect of distance from road network on myositis prevalence, but a significant effect of RUCA, possibly indicating exposure to higher level of air pollutants, consistent with previous studies that also found a significant correlation between clinically amyopathic DM with airborne pollutants ( 22 ) and urban dwellings ( 7 ). More research is needed to understand the role of proximity to roadways and air pollutants, as well as other exposures and risk factors, in the development of myositis, given the geospatial distribution of myositis patients nationwide.…”
Section: Discussionsupporting
confidence: 90%
“…Adult rheumatoid arthritis and juvenile idiopathic arthritis prevalence have both been linked to exposure to air pollution, identified by residential location near airports or road networks ( 18 21 ). Only one study has examined air pollution as a risk factor in myositis, and found a residential association with air emissions in clinically-amyopathic DM, but not classic DM ( 22 ). Exposure to air pollutants and tobacco smoking during fetal development may contribute to juvenile DM risk ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pyogenes (59) Mycobacterium tuberculosis (60) Borrelia burgdorferi (61) Ultraviolet radiation (62)(63)(64)(65)(66)(67)(68)(69)(70) Environmental pollution Silica (71)(72)(73) Dust (biological, mineral, gases/fumes) (74) Particulate matter (vehicle/industrial emissions) (75)(76)(77)(78) Cigarette smoking (79,80) Maternal exposure (associated with JDM): Chalk dust, gasoline vapor, maternal smoking, carbon monoxide (81) deemed essential for the goals of this review. We present the following article in accordance with the Narrative Review reporting checklist (available at http://dx.doi.org/10.21037/ atm-20-3719).…”
Section: Bacterialmentioning
confidence: 99%
“…In a population study of Canadian patients, the likelihood of having a systemic autoimmune disease increased with the amount of fine particulate air pollution (76). Moreover, an analysis of the geospatial distribution of DM patients in the Philadelphia metropolitan area found that point sources of airborne pollutant matter, such as emissions from industrial and commercial sources, were associated with the presence of clinically amyopathic DM, but not classic DM (78).…”
Section: Dm and Air Pollutionmentioning
confidence: 99%
“…A colorless, toxic, potentially carcinogenic, watersoluble gas, with the formula CH 2 O, having a suffocating odor, usually derived from methyl alcohol by oxidation: used chiefly in aqueous solution, as a disinfectant and preservative, and in the manufacture of various resins and plastics. The toxic effects of formaldehyde and formalin were described in literature such as bronchitis, pneumonia, gastritis, myositis [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The concept of health security corresponds to the control of risks that can alter the state of human health.…”
Section: Introductionmentioning
confidence: 99%